How the Content of Learning Videos Should Be Made? (A Study on Prospective Primary School Teacher Students During COVID-19 Pandemic) - Erfan, Muhammad; Maulyda, Mohammad Archi; Syazali, Muhammad; Umar, Umar; Sutisna, Deni (Jurnal Kiprah, 2021)
The pandemic period resulted in students having to learn from home by relying on a distance learning platform with most of the media used by educators in the form of learning videos or video conferences. This study aims to analyze how learning videos should be made so that the material contained in the learning videos can be conveyed properly to students in terms of video content, video duration, and various obstacles faced by prospective teacher students in obtaining good teaching materials in the form of learning resources and learning videos presented by educators. The data in this study were collected by means of a questionnaire distributed with Google Form. The questionnaire was distributed randomly to prospective elementary school teacher students in a study program at one of the state universities in Mataram. The questionnaire results were analyzed as a percentage of quantitative data. The results showed that 51% of respondents prefer learning videos with a duration of 5 to 10 minutes, as many as 60.5% of prospective teacher students prefer learning videos that contain material explanations of a topic of discussion than video tutorials, as well as the main obstacles for prospective teacher students in obtaining learning materials due to the limited quota of data packages and the internet network (signal) which is less supportive.